Pengembangan Portal E-Learning Berbasis Learning Management System di Sekolah Menengah Kejuruan - Mahande, Ridwan Daud; Yahya, Muh.; Mappalotten, Abd. Muis (Universitas Negeri Makassar, 2016)
This study aims to: (1) determine the steps the development of e-learning portal-based learning management system (LMS) and (2) produce an e-learning portal-based LMS in vocational high school (SMK). This study is a research and development. Methods adapted from Borg & Gall simplified into three main steps, namely: a preliminary study, development, and testing of products. Product trials conducted in class XI TKJ SMK Negeri 1 Tomoni final product resulting from the development of prototype products LMS LMS is Moodle 9.1.14 which can be accessed from anywhere they have internet access to the URL: http: //elearning.smkn1tomoni. sch.id, along with guide books LMS, LMS flowchart, diagram context LMS and LMS storyboard